Abnormal Central Venous Oxygen Saturation as a Predictor of Mortality in Patients with Sepsis and Polytrauma in the Surgical Intensive Care Unit - T Vijaya Kumar; Srinivas; A. V. Mahesh (Academia Anesthesiologica International, 2020)
Background: In postoperative heart surgery patients and patients with sepsis, pathological (low and supranormal) central venous oxygen satura- tion (ScvO2) was shown to be associated with lower mortality. The objective is we want to examine the effect of sepsis and polytrauma infection on our surgical ICU and the incidence of morbidity and death in the population. Subjects and Methods: In such patients who met the qualifying criteria and had a history of scepticism and multi-trauma, a retrospective observational review was conducted. We investigated and evaluated the association between SCV02 and mortality and other variables, such as lactate and baseline excess and period of the ICU stay and inotropic assistance within the first 6 hours, using a multivariate model review. Their entry was measured and 6 hours later. Result: The incidence of deaths in the hyperoxia group was 2.4 times higher in comparison to the general population, and the death rate in the hypoxia category was 1.25 times higher. The risk of death for the hyperoxic population was 2.4 times higher. There was no statistically relevant discrepancy of ICU, inotropic treatment, coagulopathy, dialysis, apache-11 score, baseline excess and lactate between the three levels of Scv02. Conclusion: The base excess and Scv02 were not significant when the lactates were calculated to a mortality point, but the j curve revealed that both the hypoxia group and the hyperoxia mortality had improved in contrast with the normal oxy group. Since the small sample size was sufficient to predict a trend, secondary targets were not